Government Agencies, In Search of Disputes. Issue 5 (26th April 2022) - Samuel, Adam
Abstract : Normally, dispute resolution involves two parties in conflict with each other. But the United Kingdom's financial services regulators specialize in creating schemes where there is strictly speaking only one participant: the regulated firm that has broken their rules.